2014
DOI: 10.1089/ten.tea.2012.0534
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Mesenchymal Stem Cells Enhances the Therapeutic Effects of Skeletal Myoblast Cell-Sheet Transplantation in a Rat Ischemic Cardiomyopathy Model

Abstract: Introduction: Functional skeletal myoblasts (SMBs) are transplanted into the heart effectively and safely as cell sheets, which induce functional recovery in myocardial infarction (MI) patients without lethal arrhythmia. However, their therapeutic effect is limited by ischemia. Mesenchymal stem cells (MSCs) have prosurvival/ proliferation and antiapoptotic effects on co-cultured cells in vitro. We hypothesized that adding MSCs to the SMB cell sheets might enhance SMB survival post-transplantation and improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 26 publications
1
65
0
1
Order By: Relevance
“…The most prominent findings were that ASC sheets improved systolic and diastolic functions of MI hearts under an ex-vivo condition like myoblast cell sheets. Since it has been reported that myoblasts maintain the potential of regenerating skeletal muscle during periods of stress, it suggests that myotubules could directly contribute to improvement of cardiac contraction (19). ASC sheets also improved systolic and diastolic functions of the MI hearts without their differentiation to cardiac myocytes.…”
Section: Measurement Of Cardiac Function In Isolated Perfused Heartsmentioning
confidence: 96%
“…The most prominent findings were that ASC sheets improved systolic and diastolic functions of MI hearts under an ex-vivo condition like myoblast cell sheets. Since it has been reported that myoblasts maintain the potential of regenerating skeletal muscle during periods of stress, it suggests that myotubules could directly contribute to improvement of cardiac contraction (19). ASC sheets also improved systolic and diastolic functions of the MI hearts without their differentiation to cardiac myocytes.…”
Section: Measurement Of Cardiac Function In Isolated Perfused Heartsmentioning
confidence: 96%
“…These include but are not limited to cell-sheets 3032 , fibrin patches 33, 34 , alginate scaffolds 35, 36 , and hydrogels 25, 3739 . The hyaluronic acid hydrogel was utilized in this study because of its previous effectiveness in encapsulating similarly sized peptides and its demonstrated safety in humans.…”
Section: Discussionmentioning
confidence: 99%
“…LV mass was calculated as a parameter of myocardial hypertrophy. 12,18,19 Wall stress index was defined as a parameter of LV wall stress. 20 All analyses were performed by a single investigator in a group-blinded fashion.…”
Section: Echocardiographic Assessmentmentioning
confidence: 99%
“…16,18 The equivalent total protein was loaded onto sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gels. Antibodies obtained were anti-elastin (AB 21608, 1:200 dilution; Abcam), anti-collagen I (AB34710, 1:1000 dilution; Abcam), anti-collagen II (AB3092, 1:100 dilution; Abcam), anti-matrix metalloproteinase-1 (MMP-1) (AB118529, 1:500 dilution; Abcam), anti-MMP-2 (AB51125, 1:1000 dilution; Abcam), anti-tissue inhibitor of metalloproteinase-1 (TIMP-1) (AF580, 1:500 dilution; R&D), and anti-GAPDH (AB9484; Abcam).…”
Section: Western Blotting Analysismentioning
confidence: 99%